(untitled) (Journal of Informatics and Mathematical Sciences, 2018)
Consumers’ interactions with a brand; via buying, receiving or consuming new products and services; will gradually develop the brand experiences. Because of its importance, marketers and businesses have express a great emphasis on brand experience, since it is a factor that lead to another more essential and core factor of a brand–customer relationship: brand loyalty. To clarify and examine the relationship between brand experience and brand loyalty both directly and indirectly through other factors, this research is conducted. Other factors that have their impact on this relationship are brand personality, brand trust and brand satisfaction. On the other hand, in order to provide a broad view over the relationship of brand experience and brand loyalty, the model of this research was adopted and restructured based on previous studies. The Smartphone industry was chosen for this study and the target sample was also selected accordingly in order to provide accurate responds. Quantitative method was applied for this research. The result of this research proved that there exists a positive relationship between brand experience and brand loyalty; directly and indirectly through other factors such as Brand Personality, Brand Trust and Brand Satisfaction. Based on the results, marketers should focus on enhancing their customers’ experiences; besides improving customers’ satisfaction and matching the brands’ personalities with their target customers’ in order to gain their trust. All of these efforts would contribute into building a strong brand loyalty.